Female feral fowl eject sperm of subdominant males. - Pizzari, T; Birkhead, T (2000)
Paternity is often determined by competition between the ejaculates of different males. Males can also use particular behaviours or structures to manipulate how females use sperm. However, the ability of females to bias sperm utilization in favour of preferred males independently of male manipulation has not been demonstrated. Females are predicted to respond differentially to the sperm of different males when the reproductive interests of the sexes differ and when females are coerced into copulating. Here we show that in female feral fowl most copulations are coerced, and that females consistently bias sperm retention in favour of the preferred male phenotype. Females prefer to copulate with dominant males, but when sexually coerced by subordinate males, they manipulate the behaviour of dominant males to reduce the likelihood of insemination. If this fails, females differentially eject ejaculates according to male status in the absence of any male manipulation and preferentially retain the sperm of dominant males.